(Digital) empathising: (De-)constructing (digital) empathy in foreign language teaching - Isabelle S. Thaler (Peoples' Friendship University of Russia (RUDN University), 2023)
Whilst representing a core component of any communicative context, empathy may be even more significant in foreign language teaching than other school subjects. Learners need interlocutors to use and learn a language, which makes the language-learning process even more dependent on relationships. How and where learners and users of foreign languages learn, interact and communicate with each other is increasingly shaped by digital technologies, virtual spaces and artificial intelligence-supported communication tools. This change in contexts and ways of communication also entails a change in where and how empathy is expressed. Consequently, our understanding of empathy needs to be broadened to encompass these developments and help our learners to express empathy in different contexts, media and modes. Therefore, this article will begin by delineating the etymological, empirical and theoretical background of empathy. In a second step, the significance of empathy in digital spaces will be explained, followed by a discussion of existing definitions of digital empathy and a necessary (de-) construction of (digital) empathy. Then, a preliminary model of (digital) empathising in foreign language learning will be suggested, comprising three processes: emotional, cognitive and communicative empathising. I define 'communicative empathising' as the process of communicating one's emotional and/or cognitive empathising for the other to the other - in different contexts and using various ways of communication (medium, mode).